A new species of the Amolops monticola group (Anura: Ranidae) from southwestern Yunnan, China - Yu, Guohua; Wu, Zhengjun; Yang, Junxing (Zootaxa, 2019)
We describe the new species Amolops mengdingensis sp. nov. from southwestern Yunnan, China. It belongs to the Amolops monticola species group and phylogenetically clusters together with Amolops akhaorum and Amolops archotaphus with strong support, although the relationships between these three species are not resolved. Distance between the new species and A. akhaorum is 4.7% and distance between the new species and A. archotaphus is 5.2% for 16S rRNA sequences. The new species is characterized by the following characters: distinct dorsolateral folds; side of the head dark brown with a white upper lip stripe extending to the axilla; dorsal surface smooth, except white spinules on posterior part of dorsolateral folds and above vent; top of head and dorsum green with dark spots in life; loreal region dark brown and flanks brown without any coloration of green; SVL 36.9–40.2 mm in males and 64.3 mm in female; two external subgular vocal sacs in males; vomerine teeth in two oblique ridges, separated by a small distance; pineal body absent; snout longer than eye diameter; internarial space broader than interorbital space; tympanum distinct, smaller than half of eye diameter; all fingertips expanded; two palmar tubercles; outer metatarsal tubercle absent; tibiotarsal articulation reaching beyond snout tip; near immaculate venter; limbs dorsally grayish brown with clear dark brown bars on hindlimbs; and velvety nuptial pads.